2005
DOI: 10.1002/gepi.20101
|View full text |Cite
|
Sign up to set email alerts
|

Localization of breast cancer susceptibility loci by genome‐wide SNP linkage disequilibrium mapping

Abstract: We studied the feasibility of a novel approach to localize breast cancer susceptibility genes, using a low-density genomewide panel of single-nucleotide polymorphisms and taking advantage of large regions of linkage disequilibrium (LD) flanking Jewish disease genes in high-risk cases. With Affymetrix GeneChip arrays, we genotyped 8,576 polymorphisms in three sets of Ashkenazi Jewish breast cancer cases: a ''validation'' set of 27 breast cancer cases, all of whom carried the BRCA2*6174delT founder mutation; a '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Compared with the study of Easton (18), where 390 familial breast cancer cases were screened with 227,876 SNPs, here, we used 249 familial breast cancer cases at approximately the same SNP density. In contrast to the Easton study, this study was performed on a relatively isolated population, AJs, in which we have demonstrated a significant increase in power to detect founder mutations in other genes (20). A principal components analysis (PCA) was also applied as an exclusion criteria for the familial study, in contrast to genomic control or a statistical-significance adjustment criterion method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the study of Easton (18), where 390 familial breast cancer cases were screened with 227,876 SNPs, here, we used 249 familial breast cancer cases at approximately the same SNP density. In contrast to the Easton study, this study was performed on a relatively isolated population, AJs, in which we have demonstrated a significant increase in power to detect founder mutations in other genes (20). A principal components analysis (PCA) was also applied as an exclusion criteria for the familial study, in contrast to genomic control or a statistical-significance adjustment criterion method.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have implicated a locus near FGFR2 as associated with an Ϸ1.2-fold increased risk of the disease. To add to the potential power of the GWAS approach, we have proposed and validated the use of a genetic isolate, in which larger regions of linkage disequilibrium surrounding known and putative ''founder'' mutations should increase the ability to map previously unidentified loci (20). As a first test of this approach, we have performed a GWAS study with 249 Ashkenazi Jewish (AJ) kindreds containing multiple cases of breast cancer but lacking BRCA1 or BRCA2 mutations and then replicated our findings in an independently ascertained cohort of nearly 1,000 AJ breast cancer cases and matched AJ controls.…”
mentioning
confidence: 99%
“…Several such studies are underway [Thomas et al, 2005] and a few have already been published [Ozaki et al, 2002;Maraganore et al, 2005;Shiffman et al, 2005;Duerr et al, 2006;Ellis et al, 2006;Bierut et al, 2007;Gudmundsson et al, 2007;Riley et al, 2007;Rioux et al, 2007;Sladek et al, 2007;Spinola et al, 2007;Yeager et al, 2007]. Most of the studies currently underway have adopted some form of multistage design [Satagopan and Elston, 2003], typically entailing genotyping some proportion of the sample using the entire array of SNPs and then genotyping only some subset of the most ''promising'' associations on the remaining subjects.…”
Section: Introductionmentioning
confidence: 96%
“…ModiWer genes could independently act as low penetrance genes for breast cancer susceptibility and, in the past two years, numerous genome-wide association studies have looked at breast cancer susceptibility, and have identiWed new loci such as FGFR2 (see Table 2 and Antoniou et al 2008;Easton et al 2007;Ellis et al 2006;Gold et al 2008;Huijts et al 2007;Hunter et al 2007;Murabito et al 2007;Stacey et al 2007Stacey et al , 2008. Other individuals looked at a few single nucleotide polymorphisms (SNPs) in large cohorts (Cox et al 2007a, b).…”
Section: Modiwer Genes and Low Penetrance Genesmentioning
confidence: 98%